Tumorigenic Aspects of MSC Senescence—Implication in Cancer Development and Therapy - Slavko Mojsilović (MDPI AG, 2021)
As an organism ages, many physiological processes change, including the immune system. This process, called immunosenescence, characterized by abnormal activation and imbalance of innate and adaptive immunity, leads to a state of chronic low-grade systemic inflammation, termed inflammaging. Aging and inflammaging are considered to be the root of many diseases of the elderly, as infections, autoimmune and chronic inflammatory diseases, degenerative diseases, and cancer. The role of mesenchymal stromal/stem cells (MSCs) in the inflammaging process and the age-related diseases is not completely established, although numerous features of aging MSCs, including altered immunomodulatory properties, impeded MSC niche supporting functions, and senescent MSC secretory repertoire are consistent with inflammaging development. Although senescence has its physiological function and can represent a mechanism of tumor prevention, in most cases it eventually transforms into a deleterious (para-)inflammatory process that promotes tumor growth. In this review we are going through current literature, trying to explore the role of senescent MSCs in making and/or sustaining a microenvironment permissive to tumor development and to analyze the therapeutic options that could target this process.